Pemanfaatan Sistem Informasi Manajemen dalam Pengelolaan Data Peserta Didik - Devi Riska Juliani D (JURNAL MAPPESONA, 2024)
This study aims to analyze the utilization of management information systems in managing student data at MA Al Hidayah Bakke using a qualitative approach. The primary data source was the madrasah operators. Data collection involved observation, interviews, and documentation. Data analysis techniques included data reduction, presentation, and drawing conclusions. The research findings indicate that the utilization of the management information system at MA Al Hidayah Bakke has integrated components such as hardware, software, and human resources to enhance the efficiency of madrasah data management. Support from thorough planning, facilities, and strict control ensures the quality and accuracy of the data. The data management process encompasses student data collection, continuous data processing in EMIS and SIMPATIKA systems, and data presentation through formal reports. By utilizing laptops to access EMIS and SIMPATIKA, the MIS significantly contributes to producing rapid and accurate reports, thereby improving the quality of educational services and the effectiveness of monitoring student development.